Does parity affect abdominal endurance causing low back pain among women? - Khadgi, Bimika; Acharaya, Ranjeeta Shijagurumayum; Karki, Arpita (Birat Journal of Health Sciences, 2020)
Introduction: Low back pain (LBP) is common worldwide and is leading cause of disability. Abdominal endurance promotes body posture, position, balance, urinary continence, pelvicalignment and low back health. In Nepal, women have high level physical activities and need good endurance to perform those activities. During pregnancy and postpartum,woman’s body undergoes remarkable changes up to 1 year resulting in pelvic pain, back pain and incontinence and other associated problems.Transverse abdominusis not as active as before pregnancy resulting in inadequate muscular stabilization in spine. Hence, study intends to measure abdominal endurance and compare among nulliparous, primiparous and multiparous women with association to low back pain. Objectives: To compare the abdominal endurance among nulliparous, primiparous and multiparous women and to assess the association of abdominal endurance with LBP. Methods: Non- parous and parous women of 20-30 years with 100 sample size are included tomeasure abdominal endurance by Pressure Biofeedback Unit and Nordic questionnaire was administered to identify low back pain. Results: Mean abdominal endurance found among nulliparous was 3.5mm of Hg, primiparous was 3.4mm of Hg and multiparous was 3.2mm of Hg. Chi-square test showed 45.5%nulliparous,48.5% primiparous and 52.9% multiparous women have below average abdominal endurance and 33.3%, 57.6% and 70.6% nulliparous, primiparous and multiparous women have low back pain(LBP) respectively. The association between LBP and abdominal endurance is 0.155. Conclusion: Abdominal endurance decreases with increasing parity and LBP increases with parity. Further research with large sample size is needed to explore the association between the LBP and abdominal endurance.